Transient Production of Human β-Glucocerebrosidase With Mannosidic-Type N-Glycan Structure in Glycoengineered Nicotiana benthamiana Plants - Uthailak, Naphatsamon; Kajiura, Hiroyuki; Misaki, Ryo; Fujiyama, Kazuhito (Frontiers in Plant Science, 2021)
Gaucher disease is an inherited lysosomal storage disorder caused by a deficiency of functional enzyme β-glucocerebrosidase (GCase). Recombinant GCase has been used in enzyme replacement therapy to treat Gaucher disease. Importantly, the terminal mannose N-glycan structure is essential for the uptake of recombinant GCase into macrophages via the mannose receptor. In this research, recombinant GCase was produced using Agrobacterium-mediated transient expression in both wild-type (WT) and N-acetylglucosaminyltransferase I (GnTI) downregulated Nicotiana benthamiana (∆gntI) plants, the latter of which accumulates high-mannose-type N-glycan structures. The successfully produced functional GCase exhibited GCase enzyme activity. The enzyme activity was the same as that of the conventional mammalian-derived GCase. Notably, N-glycan analysis revealed that a high-mannose-type N-glycan structure lacking plant-specific N-glycans (β1,2-xylose and α1,3-fucose residues) was predominant in all glycosylation sites of purified GCase produced from ∆gntI plants. Our research provides a promising alternative plant as a host for the production of recombinant GCase with a high-mannose-type N-glycan structure. This glycoengineered plant might be applicable to the production of other pharmaceutical proteins, especially mannose receptor targeted protein, for therapeutic uses.